Fibre Bragg grating sensors for in-situ measurement of resin pressure in curing composites - Ganapathi, A. S. (2018)
A fibre optic sensor was developed for in-situ pressure measurement based on the principle of differential pressure in liquids. This sensor system is very simple and consists of fibre Bragg grating (FBG) done on a fibre with core diameter of 9 μm. A calibration study was carried out with a water column and the pressure sensitivity was found to be 1.636 × 10-2MPa-1. The results show that response of FBG to the rise of water level is linear and agrees well with the theoretical results. The reliability of the sensors is confirmed by repeating the measurements for three times. The sensor is useful in applications that involve in-situ resin pressure measurement in manufacturing of laminated composite materials.